Economic and energy viability of sunflower irrigated crop - Gomes, Eder P.; Sanches, Arthur C.; de Azevedo, Edéria P.G. [UNESP]; Geisenhoff, Luciano O.; Jordan, Rodrigo A. (FapUNIFESP (SciELO), 2018)
This study was carried out with the objective of assessing grain yield, economic analysis and energy balance of three sunflower genotypes with and without irrigation. The experiment was installed in the Experimental Farm of the Faculty of Agrarian Sciences of the Federal University of Grande Dourados in the 2011/2012 and 2012/2013 harvests in Dourados-MS, Brazil. The experimental design used was a random complete block design with subdivisions, with and without irrigation (plots), with three genotypes (subplots) and four replications, constituting 24 plots. There were no differences in productivity among the genotypes. The irrigation increased the operational cost of the sunflower crop production, but it did not economically obstruct the activity, due to the increase of productivity of 74.5% and 30% in the harvests of 2011/2012 and 2012/2013. The energy ratios of the sunflower crop were not altered by irrigation, equal to 5.7 and 8.7 in the harvests of 2011/2012 and 2012/2013, respectively.
Keywords: Central pivot; Energy depreciation; Helianthus annuus L.; Operating cost of production